Advanced Therapy Medicines Based on Oncolytic Viruses (Part II: Development and Authorisation of IMLYGIC®) - E. V. Melnikova; O. A. Rachinskaya; V. A. Merkulov (Регуляторные исследования и экспертиза лекарственных средств, 2021)
The only oncolytic virus-based product authorised in the US and EU—IMLYGIC®, a genetically modified herpes simplex virus type 1 (by BioVex Inc., a subsidiary of Amgen, Inc.)—was developed and approved for clinical use as monotherapy for recurrent unresectable melanoma. The aim of the study was to analyse materials on IMLYGIC® development and authorisation in order to be able to use the data on specific aspects of preclinical and clinical trials of oncolytic virus-based products in the development of regulatory framework for Russia and the EAEU. The publicly available preclinical and clinical trial results demonstrate a decrease in the size of both tumours being injected and remote tumours/skin lesions, which supports the local and systemic effects of IMLYGIC® due to the lysis effect of the virus on the tumour cells. The clinical trials of IMLYGIC® were the first to use the durable response rate, and not the overall survival, as the primary endpoint of the efficacy of the anticancer drug. Benefits of IMLYGIC® therapy were observed across all the secondary endpoints, except overall survival. Significant efficacy of the drug therapy was demonstrated only in patients without visceral lesions, which resulted in limitations of indications for use. There have been no serious or severe adverse effects associated with IMLYGIC®. If symptoms of viral infection develop, they can be neutralized thanks to the product’s sensitivity to acyclovir. At present, advanced therapy medicinal products derived from an oncolytic virus may be authorised in Russia for clinical use as monotherapy or combination therapy, according to the EAEU regulations.